Hydrogen assisted cracking of AISI 4137M steel in O&G environments. (21st December 2015) - Thodla, Ramgopal; Piza Paes, Marcelo T.; Gerst, Brandon
Abstract: Hydrogen assisted cracking of AISI 4137M material was studied in a range of conditions. 4137M steel was studied under cathodic protection (CP) charging conditions as a function of applied potential. The fracture toughness of AISI 4137M decreases dramatically with applied cathodic potential and was low as 45 MPa√m. The crack morphology was intergranular in nature. The application of a slight ripple load lead to stable crack propagation at even lower values of K. The effect of lower pH and CO2 concentration were also evaluated and it was found that stable crack propagation could occur at low values of K in the presence of a ripple load. Under ripple loading stable crack propagation was possible at a ΔK of ∼136 Nmm −3/2 (∼4 MPa√m). Further testing performed under low pH conditions to simulate possible chemistry in the threads due to trapped seawater along with the high CO2 content in the gas, suggests that it is possible to stable crack propagation under ripple loading in low pH environments. Hydrogen flux measurements were performed to co-relate the behavior of the observed Kth and the various environmental parameters. Slow strain rate tests were performed in high pressure CO2 environments, in which increased cracking susceptibility was observed. Diffusible hydrogen measurements were performed on SSR samples tested and the %elongation measured was found to be related to the diffusible H concentration. Highlights: Fracture toughness and corrosion fatigue of 4137M steel in oil and gas production environments. Role of hydrogen on Kth and crack growth rate behavior. Corrosion fatigue under cathodic potentials and the effect of frequency on hydrogen assisted corrosion fatigue.